2006
DOI: 10.3349/ymj.2006.47.6.799
|View full text |Cite
|
Sign up to set email alerts
|

The CobraPLA™ During Anesthesia with Controlled Ventilation: A Clinical Trial of Efficacy

Abstract: TM(CPLA) is a relatively new supraglottic airway device that has not been sufficiently investigated.Here, we performed a prospective observational study to evaluate the efficacy of the CPLA during controlled ventilation. In 50 anesthetized and paralyzed patients undergoing elective surgery a CPLA was inserted and inflated to an intracuff pressure of 60 cm H2O. The success rate of insertion upon the first attempt was 82% (41/50), with a mean insertion time of 16.3 ± 4.5 seconds. The adequacy of ventilation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…This too was consistent with other studies [25]. In this study, the first attempt success rate of the PLA at 88% was similar to this of Nam et al [6] at 82%, who used muscle relaxants. The first attempt insertion success rate with the LT was higher at 96%, which was similar to the findings of Wrobel at al.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This too was consistent with other studies [25]. In this study, the first attempt success rate of the PLA at 88% was similar to this of Nam et al [6] at 82%, who used muscle relaxants. The first attempt insertion success rate with the LT was higher at 96%, which was similar to the findings of Wrobel at al.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the overall success rate was 100% for both. This was consistent with other reports, where the success rate of insertion ranged between 92 and 100% for the LT [12,[19][20][21][22][23][24] and between 95 and 100% for the PLA [4][5][6][25][26][27][28]. Despite the high success rate of insertion we found that the PLA was more difficult to insert than the LT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The primary outcome was the airway leak pressure. The sample size was based on previous studies with the CobraPLA [4] and was selected to detect a projected difference of 5 cmH 2 O between the groups with respect to airway leak pressure for a type I error of 0.05 and power of 0.9. For detailed comparison, secondary outcomes included the time for insertion, the number of insertion and reposition attempts, the anatomical position as determined by fibreoptic bronchoscopy, and peak and plateau airway pressure during controlled ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…One of these devices, the CobraPLA Ò (Engineered Medical Systems, Inc., Indianapolis, IN, USA) is a relatively new supraglottic airway device that has been proven safe and effective in several clinical settings [1][2][3][4][5][6][7]. However, to the best of our knowledge, there is only one study that compares the performance of the CobraPLA with that of other supraglottic airways in paralysed patients and it did not examine the airway leak pressure.…”
mentioning
confidence: 99%